ASEAN Contemporary Security: Maritime Diplomacy in Handling of Maritime Security Threats in Malaka Strait - Laode Muhamad Fathun (Insignia: Journal of International Relations, 2019)
Abstract This paper will explain the consequences of Indonesia's geopolitical location, namely in the Malacca Strait as an international trade route. The Malacca Strait is a crossing route for foreign ships to distribute goods to various regions. However, the strategic channel not only attracts sympathy from international entrepreneurs but also attracts these criminals and hijackers to obtain economic results from this activity. The Malacca Strait strategically makes pirates and pirates criminalize passing ships. On the other hand, the consequences of state legal matters are maintaining security and safety, and the comfort of crossings in the Malacca Strait. With a number of problems, both defense, governance and management infrastructure that cannot be seen in a fixed manner. In addition, its position borders on three countries, namely Indonesia, Malaysia and Singapore. With a qualitative descriptive analysis method, this paper explains the need for bilateral, trilateral and regional multi-level diplomacy approaches to solve problems. And the purpose of this article is that piracy occurred in the Straits of Malacca because of its strategic geopolitical structure and weak Indonesian defense. So, collaboration is needed, coordination through diplomacy and military projections as an effort to safeguard the sea area, sea control and military defense articulation. Thus, the authors hope that this article can add knowledge to the study of international relations, especially in marine studies. Keywords: Geopolitics, Maritime State, Malacca Strait, Piracy, Multilevel Diplomacy Abstrak Paper ini akan menjelaskan konsekuensi dari lokasi geopolitik Indonesia, yaitu di Selat Malaka sebagai rute perdagangan internasional. Selat Malaka adalah rute penyeberangan bagi kapal-kapal asing untuk mendistribusikan barang ke berbagai daerah. Namun, saluran strategis tidak hanya menarik simpati dari pengusaha internasional tetapi juga menarik para pelaku kejahatan dan pembajak ini untuk mendapatkan hasil ekonomi dari kegiatan ini. Selat Malaka yang strategis membuat perompak dan pembajak mengkriminalkan kapal yang lewat. Sisi lain, konsekuensi dari urusan hukum negara adalah menjaga keamanan dan keselamatan, dan kenyamanan penyeberangan di Selat Malaka. Dengan sejumlah masalah baik pertahanan, tata kelola, infrastruktur manajemen yang tidak bisa dilihat secara secara terpisa. Selain itu posisinya berbatasan dengan tiga negara yaitu Indonesia, Malaysia dan Singapura. Dengan metode analisis deskriptif kualitatif, makalah ini menjelaskan perlunya pendekatan diplomasi multi-level bilateral, trilateral dan regional untuk menyelesaikan masalah. Dan tujuan dari artikel ini bahwa pembajakan terjadi di Selat Malaka karena struktur geopolitik yang strategis dan pertahanan Indonesia yang lemah. Jadi, diperlukan kolaborasi, koordinasi melalui diplomasi dan proyeksi militer sebagai upaya untuk menjaga wilayah laut, kontrol laut dan artikulasi pertahanan militer. Dengan demikian, penulis berharap bahwa artikel ini dapat menambah pengetahuan untuk studi hubungan internasional khususnya dalam studi kelautan. Kata kunci: Diplomasi Multilevel, Geopolitik, Negara Maritim, Pembajakan, Selat Malaka